Vers une approche simplifiée pour introduire le caractère incrémental dans les systèmes de dialogue - Khouzaimi, Hatim; Laroche, Romain; Lefevre, Fabrice (Proceedings of the 21st Conference sur le Traitement Automatique des Langues Naturelles (TALN), 2014)
Incremental dialogue is at the heart of current research in the field of dialogue systems. Several architectures and models have been published such as (Allen et al., 2001; Schlangen & Skantze, 2011). This work has made it possible to understand many aspects of incremental dialogue, however, in order to implement these solutions, one needs to start from scratch as the existing architectures are inherently different. Our approach is different as it tends towards a new generation of incremental systems that behave incrementally but work internally in a traditional way. This paper suggests inserting a new module, called the Scheduler, between the service and the client. This Scheduler manages the asynchronous events, hence reproducing the behaviour of incremental systems from the client’s point of view. On the other end, the service does not work incrementally.